Demographic, clinical, and microbial aspects of chronic and aggressive periodontitis in Colombia: A multicenter study (2007)
The microbial profile of periodontal disease varies among different human populations. This study evaluated the demographic, clinical, and microbiologic aspects of periodontitis in a multigeographic sample in Colombia. Three hundred twenty-five patients with chronic periodontitis (CP), 158 patients with aggressive periodontitis (AgP), and 137 healthy-gingivitis controls from five regions of the country were studied. Clinical, microbial, and sociodemographic data were collected. Microbiologic identification was performed using polymerase chain reaction 16S rRNA gene on pooled subgingival samples, and the presence of Gram-negative enteric rods was evaluated by culture. Bivariate and multivariate logistic regression analyses were conducted. Porphyromonas gingivalis occurred in 71.5% of individuals with periodontitis, Tannerella forsythensis occurred in 58.5%, Campylobacter rectus occurred in 57.5%, Actinobacillus actinomycetemcomitans occurred in 23.6%, and enteric rods occurred in 34.5%. P. gingivalis was more common in CP and AgP than controls. A. actinomycetemcomitans was increased in AgP compared to controls and patients with CP. T. forsythensis, C. rectus, and Eikenella corrodens had a low presence in the West Pacific and Central regions, and enteric rods were increased in the Central region (P <0.05). Other sociodemographic factors were not associated with these microorganisms. Geographic regions do not influence the microbiota, but the microbiota may vary by geographic region. P. gingivalis, T. forsythensis, and C. rectus are the most prevalent periodontophatic microorganisms in Colombia. A. actinomycetemcomitans was more common in AgP, and a large percentage of the population studied had enteric rods in the subgingival plaque.